A Natural Alternative: The Development and Testing of Herbal-Based Hand Sanitizers with Antibacterial Properties - Wiranti, Iin; Hidayah, Nurul; Fardani, Nawa Naufa (Indonesian Journal of Medical and Pharmaceutical Science, 2025)
Background: Hand hygiene plays a crucial role in preventing the spread of infections, making effective hand sanitizers essential. However, concerns about skin irritation and microbial resistance associated with synthetic ingredients have increased the demand for natural, plant-based alternatives. This study aimed to formulate and evaluate plant-based hand sanitizers containing ethanol, lemongrass essential oil, and aloe vera gel for their organoleptic properties, pH, and antibacterial activity. Methods: The prepared formulations exhibited acceptable organoleptic characteristics, with variations in odor and texture based on essential oil and aloe vera concentrations. Results: The pH values of all formulations were within the skin-friendly range, ensuring safe application. Antibacterial testing against Escherichia coli demonstrated that formulations with higher ethanol and lemongrass oil concentrations exhibited the largest inhibition zone (13,67±0,58 mm), while aloe vera contributed to skin-conditioning properties. Although the formulations were effective, none surpassed the inhibition zone of the positive control. Conclusion: This study suggests that the prepared natural hand sanitizer gel with Aloe vera and lemongrass essential oil can be a potential alternative to enhance the antibacterial efficacy of hand sanitizers while maintaining user comfort.